2009
DOI: 10.1021/ol902314z
|View full text |Cite
|
Sign up to set email alerts
|

Spirobifluorene-Bridged Donor/Acceptor Dye for Organic Dye-Sensitized Solar Cells

Abstract: A new dye, SSD1, featuring two donor/acceptor chromophores aligned in a spiro configuration with two anchoring groups separated at a distance of 10.05 A (closely matching the distance between the adsorption sites of the anatase TiO(2) surface) undergoes efficient dye adherence on TiO(2) films. A dye-sensitized solar cell incorporating SSD1 exhibited a short-circuit current of 8.9 mA cm(-2), an open-circuit voltage of 0.63 V, a fill factor of 0.67, and a power conversion efficiency of 3.75%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 29 publications
5
77
0
Order By: Relevance
“…Another approach to nonconjugated multi‐donor multi‐anchoring sensitizers was based on the use of a spiro structure. The structure of dye 54 displays the best match between the separation of the anchoring sites and the TiO 2 surface adsorption sites 42. The synthesis of this dye was developed around the functionalized spiro core, to which the donor groups are first connected, followed by final condensation with cyanoacetic acid.…”
Section: Design and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to nonconjugated multi‐donor multi‐anchoring sensitizers was based on the use of a spiro structure. The structure of dye 54 displays the best match between the separation of the anchoring sites and the TiO 2 surface adsorption sites 42. The synthesis of this dye was developed around the functionalized spiro core, to which the donor groups are first connected, followed by final condensation with cyanoacetic acid.…”
Section: Design and Synthesismentioning
confidence: 99%
“… Geometric disposition of a typical spiro structure, compound 54 , on the TiO 2 surface. Reprinted from ref.,42 copyright 2010, with permission from the American Chemical Society. …”
Section: Optical and Photovoltaic Propertiesmentioning
confidence: 99%
“…Triarylamine has been by far the most widely used D core. [8] In the search for improved optical and structural properties, we, [9] and others, [10,11] have recently introduced a novel model class of dibranched dianchoring organic sensitizers composed of one donor and two anchoring groups (A-π-D-π-A). We have shown that the dibranched dye DB-1 (Scheme 1) offers improved optical properties (higher molar extinction coefficients and red-shifted absorption), increased photocurrent, and enhanced stability compared to its monobranched analogues.…”
Section: Introductionmentioning
confidence: 99%
“…An effective way to control the p-stacked aggregation and the resulting charge recombination is the utilization of sensitizers with two anchoring units into a spiro configuration, similar to Ru sensitizers [8]. Sensitizers of this type have the potential to strengthen their binding onto the TiO 2 surface and increase their absorbed amount, which in turn induces efficient electron injection resulting in an improvement of DSSC performance [8][9][10]. Indeed, when two or more organic dyes with double or multiple anchoring groups have been used as sensitizers, DSSCs with enhanced photoresponses, and stabilities were obtained [9a,11].…”
Section: Introductionmentioning
confidence: 99%